2015
DOI: 10.1007/s00464-015-4225-7
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of excess weight loss after laparoscopic Roux-en-Y gastric bypass: data from an artificial neural network

Abstract: Introduction Laparoscopic Roux-en-Y Gastric Bypass (LRYGB) has become the gold standard for surgical weight loss. The success of LRYGB may be measured by excess body-mass index loss (%EBMIL) over 25 kg/m2, which is partially determined by multiple patient factors. In this study, artificial neural network (ANN) modeling was used to derive a reasonable estimate of expected postoperative weight loss using only known preoperative patient variables. Additionally, ANN modeling allowed for the discriminant prediction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 35 publications
3
39
2
1
Order By: Relevance
“…The literature has been unclear on this issue and we hope our study ultimately helps determine whether or not if affects weight loss after RYGB. (10,27) We also did not find GERD to be a factor which agrees with previously published literature for the RYGB (28). Sleep apnea has not previously been shown to effect weight loss in studies which agrees with our results as sleep apnea was not found to be a significant factor.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The literature has been unclear on this issue and we hope our study ultimately helps determine whether or not if affects weight loss after RYGB. (10,27) We also did not find GERD to be a factor which agrees with previously published literature for the RYGB (28). Sleep apnea has not previously been shown to effect weight loss in studies which agrees with our results as sleep apnea was not found to be a significant factor.…”
Section: Discussionsupporting
confidence: 92%
“…Literature is split on whether hypertension effects weight loss however in our study we found that it had no effect on eventual weight loss (10,29,30).…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Initial BMI has been the pre-operative factor most consistently predictive, however, comorbidities such as hypertension, diabetes and psychiatric disorders, as well as race, gender and the presence of pre-operative weight loss have all been reported as well. 3, 6, 2628 In this study, 547 LRYGB patients over a ten year period from a single institution were retrospectively reviewed to test our hypothesis that RDW may predict EBMIL. We aimed to determine the association between RDW and EBMIL, however, there was a need to control for the baseline demographics of gender, age and BMI 0 such that any significance in our suspected correlation could have wide applicability and validity.…”
Section: Discussionmentioning
confidence: 99%
“…35 Of the commonly performed bariatric operations, the Roux-en-Y gastric bypass is perhaps the most effective, consistently leading to sustained weight loss in the compliant patient. 6 It is typically performed laparoscopically, with few complications and rapid recovery. In anticipation of this operation, routine pre-operative blood work is often conducted to assess the patient’s iron stores, as post-operative anemia is a common, recognized sequela.…”
Section: Introductionmentioning
confidence: 99%